2015
DOI: 10.1038/nmeth.3406
|View full text |Cite
|
Sign up to set email alerts
|

Probing a cell-embedded megadalton protein complex by DNP-supported solid-state NMR

Abstract: Studying biomolecules at atomic resolution in their native environment is the ultimate aim of structural biology. We investigated the bacterial type IV secretion system core complex (T4SScc) by cellular dynamic nuclear polarization-based solid-state nuclear magnetic resonance spectroscopy to validate a structural model previously generated by combining in vitro and in silico data. Our results indicate that T4SScc is well folded in the cellular setting, revealing protein regions that had been elusive when studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
155
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 131 publications
(155 citation statements)
references
References 32 publications
0
155
0
Order By: Relevance
“…The obtained results are also of interest for their implications for variable temperature studies of membrane-bound proteins and peptides, as well as whole cells, by MAS ssNMR. This notably includes the ongoing efforts to apply low-temperature dynamic nuclear polarization (DNP) to membrane-embedded proteins and whole cells (69,70).…”
Section: Discussionmentioning
confidence: 99%
“…The obtained results are also of interest for their implications for variable temperature studies of membrane-bound proteins and peptides, as well as whole cells, by MAS ssNMR. This notably includes the ongoing efforts to apply low-temperature dynamic nuclear polarization (DNP) to membrane-embedded proteins and whole cells (69,70).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that DNP can drastically increase the sensitivity in solid-state NMR (ssNMR) experiments (Ni et al 2013;Sauvee et al 2013;Song et al 2006) and it has been successfully applied to several biological systems (Becker-Baldus et al 2015;Debelouchina et al 2013;Fricke et al 2015;Gupta et al 2016;Kaplan et al 2015;Koers et al 2014;Potapov et al 2015). Unfortunately, those experiments need to be carried out at cryogenic temperatures as the enhancement factor decreases with increasing temperature (Rosay et al 2010;Sauvee et al 2013;Zagdoun et al 2013).…”
Section: Contentmentioning
confidence: 99%
“…The development of a general nuclear hyperpolarization technique at arbitrary fields would enable measurements of biomolecules and reaction dynamics that were not accessible by the present techniques while decreasing routine NMR measurement times by orders of magnitude [1]. Several approaches to dynamic nuclear polarization (DNP) processes have been demonstrated that enhance nuclear spin polarization; however, the majority are limited to specific fields [2][3][4][5], low temperatures [6,7], specific molecules [8], or require microwave irradiation of the sample [8,9]. Low temperature is particularly problematic for liquid-state biological samples, where freezing leads to a loss of spectral resolution [10].…”
Section: Introductionmentioning
confidence: 99%